Fabrication and Characterization of SnS2Nanosheets/ITO-Glass Based Visible Band Photodetector - Mani Yadav S.; Pandey A. (My University, 2025)
This paper reports the fabrication and characterization of visible band SnS2/ITO-glass based photodetector. The simple and low cost hydrothermal technique has been used to synthesize high crystalline SnS2 nanosheets. The synthesized 2D-SnS2 nanosheets have been patterned over high conducting ITO coated glass substrate working as a charge transport layer. The optical parameters of the device are measured for ~640 nm illumination wavelength with low optical power density. The responsivity, sensitivity and EQE(%) of the device for this illumination wavelength are found to be 0.5 (A/W), 4 and 97%, respectively. The broad visible range absorption of synthesized SnS2 nanosheets may leads its applications in the field of solar cell and optical imaging. © 2020 IEEE.